Concept of Bilinear Transformation, Jacobian, and Conformal Mapping with Applications - Kumar, Nand Kishor; Yadav, Dipendra Prasad (Mikailalsys Journal of Advanced Engineering International, 2024)
This article explores the concepts of bilinear transformation, Jacobian transformation, and conformal mapping, focusing on their essential properties and presenting key results. The discussion revolves around isogonal transformation, conformal transformation, Jacobian transformation, and bilinear transformation, as well as critical points and fixed points.